Protegrin interaction with lipid monolayers: Grazing incidence X-ray diffraction and X-ray reflectivity study - Neville, Frances (2008)
Interactions of the antimicrobial peptide protegrin-1 (PG-1) with phospholipid monolayers have been investigated by using grazing incidence X-ray diffraction (GIXD) and specular X-ray reflectivity (XR). The structure of a PG-1 film at the air-aqueous interface was also investigated by XR for the first time. Lipid A, dipalmitoyl-phosphatidylglycerol (DPPG) and dipalmitoyl-phosphatidylcholine (DPPC) monolayers were formed at the air-aqueous interface to mimic the surface of the bacterial cell wall and the outer leaflet of the erythrocyte cell membrane, respectively. Experiments were carried out under constant area conditions where the pressure changes upon insertion of peptide into the monolayer. GIXD data suggest that the greatest monolayer disruption produced by PG-1 is seen with the DPPG system at 20 mN/m since the Bragg peaks completely disappear after introduction of PG-1 to the system. PG-1 shows greater insertion into the lipid A system compared to the DPPC system when both films are held at the same initial surface pressure of 20 mN/m. The degree of insertion lessens at 30 mN/m with both DPPC and DPPG monolayer systems. XR data further reveal that PG-1 inserts primarily in the head group region of lipid monolayers. However, only the XR data of the anionic lipids suggest the existence of an additional adsorbed peptide layer below the head group of the monolayer. Overall the data show that the extent of peptide/lipid interaction and lipid monolayer disruption depends not only on the lipid composition of the monolayer, but the packing density of the lipids in the monolayer prior to the introduction of peptide to the subphase.